Pengaruh Media E-Learning Quipper School pada Pembelajaran Berbasis Masalah untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik - Selvianti H, Fifi; Sulastry, Taty; Herawati, Netti (Chemistry Education Review (CER), 2021)
The purpose of this study is to determine whether or not there is an influence of Quipper School e-learning media on a problem-based learning model to increase motivation and learning outcomes of students in grade X MIPA 1 at MAN Sidenreng Rappangin Chemical Bonding subject. This research is a quasi-experimental research, quantitative with experimental research methods. The design used in this study was a randomized pretest-posttest design. The data obtained were analyzed by employing descriptive and inferential statistical analysis by using SPSS version 15. From the data analysis, it is discovered that the average value of motivation and learning outcomes of the experimental class is greater than that of the control class. In addition, from testing the T test hypothesis, a significance value of 0.001 < 0.05 is obtained for motivation and 0.000 < 0.05 for learning outcomes, which means that motivation and group learning outcomes using the Quipper School e-learning media on the PBM model have an influence compared to the group without using the Quipper School e-learning media on the PBM model.